Cu@Ni core–shell nanoparticles/reduced graphene oxide nanocomposites for nonenzymatic glucose sensor. Issue 34 (12th April 2017) - Wu, Kong-Lin; Cai, Ya-Miao; Jiang, Bin-Bin; Cheong, Weng-Chon; Wei, Xian-Wen; Wang, Weizhi; Yu, Nan
Abstract : Cu@Ni core–shell nanoparticle decorated reduced graphene oxide nanocomposites are prepared and further employed as a novel sensing material for fabricating a sensitive nonenzymatic glucose sensor with excellent performance for glucose. Abstract : In this work, the Cu x @Ni100− x core–shell nanoparticles (CSNPs) are deposited on reduced graphene oxide (rGO) sheets, and this nanocomposites (in a Nafion matrix) are shown to be a viable materials for nonenzymatic sensing of glucose. A novel nonenzymatic glucose sensor based on a glass carbon electrode modified with Cu53 @Ni47 CSNPs/rGO (referred to as Cu53 @Ni47 CSNPs/rGO/GCE) displays an enhanced electrocatalytic activity to glucose oxidation in 0.1 M NaOH solution than that of Cu/GCE, Ni/GCE, Cu/rGO/GCE, Ni/rGO/GCE, and Cu52 @Ni48 CSNPs/GCE, respectively. This is attributed to the three-in-one synergetic effects from their bimetallic compositions, specific core–shell structures, and interactions from the bimetallic CSNPs and support materials of rGO sheets. At an applied potential of +0.575 V ( vs. SCE), the electrode has a low detection limit (0.5 μM; S/N = 3), a very wide linear range (0.001 mM to 4.1 mM), high sensitivity (780 μA mM −1 cm −2 ), and a fast response time (3 s). Thus, it has great potential for the development of nonenzymatic glucose sensors.